2013
DOI: 10.4067/s0716-97602013000300005
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous administration of bone marrow-derived multipotent mesenchymal stromal cells has a neutral effect on obesity-induced diabetic cardiomyopathy

Abstract: Obesity is a major global health issue. Obese patients develop metabolic syndrome, which is a cluster of clinical features characterized by insulin resistance and dyslipidemia. Its cardiac manifestation, diabetic cardiomyopathy, leads to heart failure. Bone marrow-derived multipotent mesenchymal stromal cells, also referred to as mesenchymal stem cells (MSC) are envisioned as a therapeutic tool not only for cardiovascular diseases but also for other degenerative conditions. Our aim was to evaluate whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…It was reported that intramyocardial transplantation of nondiabetic MSC has a protective effect on diabetic hearts . However, not all studies have consistently shown that stem cells from nondiabetic animals can improve the function of diabetic hearts . In this study, we tested the effects of diabetes on post‐AMI myocardial repair in the presence of stem cell therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that intramyocardial transplantation of nondiabetic MSC has a protective effect on diabetic hearts . However, not all studies have consistently shown that stem cells from nondiabetic animals can improve the function of diabetic hearts . In this study, we tested the effects of diabetes on post‐AMI myocardial repair in the presence of stem cell therapy.…”
Section: Discussionmentioning
confidence: 99%
“…IV administration of allogeneic bone marrow-derived MSCs with a single dose of 0.5 × 10 6 or three consecutive monthly doses of 0.5 × 10 6 MSCs did not result in improved cardiac function when assessed 4 months later but rather has a neutral effect on DC. The observed effects may be as a result of the route, time, and dose used but possibly also to issues with efficient homing and engraftment of the tail vein administered cells (149). …”
Section: Msc-based Therapies For Other Diabetic Complicationsmentioning
confidence: 99%
“…All data presented herein were obtained from refs. [44,54,55,70,72,74,75,78,88,95,96,98,[102][103][104][105][106][107][108][109][110][111]116,[119][120][121][124][125][126][127][128][129][130]132,[134][135][136][137][140][141][142][143][144][147][148][149][150][151][152][153][154]…”
Section: Resultsmentioning
confidence: 99%
“…[45,88,[92][93][94][99][100][101][102] Conversely, very long periods of diet exposure, that is, over 32 weeks, appear not to promote higher significant differences in the impairment of the animals' metabolic parameters compared to 12-24 weeks of exposure and seem to be less efficient in the development of MetS in mice (Table 4). [95][96][97][98]103] Van der Heijden et al evaluated C57BL/6J male mice fed with HFD (45% kcal from fat) for 24, 40, or 52 weeks and showed a rapid increase in body weight, which was significant from 12 weeks following a diet onward. Prolonged HFD feeding led to an additional, albeit slight, increase in body weight of up to 40 weeks and remained stable until the end of the study.…”
Section: Exposure Time To Dietmentioning
confidence: 99%
See 1 more Smart Citation